A regenerative approach using xenograft and PRF membrane in the management of muscosal fenestration in posterior maxilla - A rare case report - Swapnil Sanjay Karwa; Lalitha Basappa Shiggaon; Alka Sanjay Waghmare; Mayur Ashok Dhavan (Wolters Kluwer Medknow Publications, 2021)
Mucosal fenestration is a rare entity wherein apex of the tooth is exposed in the oral cavity due to breakdown of the overlying bone and mucosa. This leads to accumulation of plaque and if left untreated can hamper the further prognosis of the tooth. Although there are few evidences regarding mucosal fenestrations in posterior region of maxilla, treatment of the same have been challenging for the clinicians. This case report describes the management of mucosal fenestrations in the posterior maxilla by regenerative periodontal flap surgical approach using xenograft (Osseograft) and platelet-rich fibrin membrane.